A Facile Route to Pyrazolo[1, 2‐a]cinnoline via Rhodium(III)‐catalyzed Annulation of Pyrazolidinoes and Iodonium Ylides. Issue 1 (1st December 2021) - Yang, Zi; Zhou, Yi; Li, Haigang; Lei, Jieni; Bing, Pingping; He, Binsheng; Li, Yaqian
Abstract: A rhodium(III)‐catalysed cascade C−H bond activation/intramolecular cyclization of pyrazolidiones with iodonium ylide has been described, leading to the formation of various pyrazolo[1, 2‐a]cinnolines. Herein, iodonium ylide serves as a carbene precursor. This protocol exhibits good regioselectivity and high functional group tolerability under mild reaction conditions. Abstract : A simple and efficient procedure to pyrazolo[1, 2‐a]cinnoline starting from easily available pyrazolidiones and iodonium ylide via a rhodium‐catalyzed [4+2] annulative coupling reaction is presented.